2009
DOI: 10.1161/circinterventions.108.847459.108.847459
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Disease Burden and In-Hospital Outcomes Among Patients Undergoing Percutaneous Coronary Intervention in New York State

Abstract: Background— The presence of atherosclerosis in extracardiac vascular beds is associated with an increased risk of adverse cardiovascular outcomes among stable patients with coronary artery disease (CAD). However, there is little data regarding the impact of the presence and extent of vascular disease on outcomes in patients with CAD undergoing percutaneous coronary intervention. Methods and Results— We analyzed 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Several studies in the BMS era concluded that PVD was an independent predictor of adverse outcomes after PCI . Nikolsky et al examined 12‐month outcomes in 10,440 consecutive patients undergoing PCI in the BMS era, 1,969 of whom had symptomatic lower extremity PVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the BMS era concluded that PVD was an independent predictor of adverse outcomes after PCI . Nikolsky et al examined 12‐month outcomes in 10,440 consecutive patients undergoing PCI in the BMS era, 1,969 of whom had symptomatic lower extremity PVD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a reduction in the rate of repeat PCI, their risk of major adverse cardiovascular events (MACEs) outcomes following PCI has remained unchanged across the early bare‐metal stent (BMS) and drug‐eluting stent (DES) eras . While PVD is recognized as an independent predictor of poor outcomes after PCI in the BMS era, there is a paucity of data within the DES era . This study aimed to evaluate whether PVD is an independent predictor of adverse outcomes in patients undergoing PCI in a contemporary setting.…”
Section: Introductionmentioning
confidence: 99%
“…8 In particular, polyvascular disease that includes atherosclerosis of multiple vascular beds is associated with higher risk of recurrent ischemic events and warrants special attention. 911 To address these issues, we evaluated a panel of inflammatory, platelet, and lipid biomarkers as independent predictors of symptomatic PAD in a cohort of patients with coronary disease or their risk equivalent receiving atorvastatin who were randomized to receive darapladib or placebo. 12 Darapladib is a selective lipoprotein-associated phospholipase A 2 (Lp-PLA 2 ) inhibitor that is under investigation for its potential to stabilize high-risk atherosclerotic plaques and potentially reduce cardiovascular events.…”
mentioning
confidence: 99%
“…Completeness of revascularization by PCI is often limited by the chance of technical success in treating adverse lesions such as chronic occlusions. Patients in whom complete revascularization is most difficult are often those at highest risk, because complex coronary anatomy is frequently associated with clinical risk factors such as age, diabetes, renal impairment, and extra‐cardiac arteriopathy . Many of these patients are therefore also not fit to undergo CABG.…”
Section: Introductionmentioning
confidence: 99%